Policy in the Making: Establishing Public Policy for Complex Animal Diseases - Beilke, Elizabeth M. (My University, 2015)
The goal of this review is to provide an overview of the process by which policy is developed for complex animal diseases. There is no one size fits all approach to policy. Policy making for a disease is complex, often a bit disorderly, and like medicine not an exact science. The current mission behind the United States Department of Agriculture, Animal and Plant Health Inspection Service, Veterinary Services (USDA, APHIS-VS) and its role in the One Health partnership is to adequately contribute to the animal health component. One Health is a crucial component behind the response to any emerging disease because of the interrelatedness of animal, human, and environmental health. The following document strives to further support the advancement of the One Health concept as it relates to complex animal diseases. This review also illustrates just what can happen when a student becomes an integrated part of One Health and public policy. Throughout the development of this paper, I found myself diving right into the very concepts that I had previously only seen and heard in the classroom. This paper serves not only as an APHIS training document, but as substantial evidence of how a field experience can turn an array of concepts into a workable puzzle by which one builds a career dedicated to One Health.
Keywords: Policy; Health; Emerging; Infectious; Veterinary; Disease; Public Health (0573)